Effect of COVID 19 pandemic on the academic performance of physical therapy students - Ahmed Ali Mohammed Torad; Omnia Ahmed; Reham ElKalla (Journal of the Pakistan Medical Association, 2023)
Objective: To examine the impact of university closure and recourse to internet-based learning on the academic achievement of physical therapy students. Method: The retrospective study was conducted at Kafrelsheikh University, Egypt, and comprised academic grades of physical therapy students related to pre-coronavirus disease-2019 pandemic academic year 2019-2020 in group 1 and per-pandemic 2020-2021 session group 2. Data was analysed using SPSS 26. Results: Of the 8,190 students, 4,764(58.2%) were females and 3,426(41.8%) were males with age range 17-23 years who were studying at 5 academic levels. There were 3,732(45.6%) students in group 1 and 4,458(54.4%) in group 2. There were significant difference in the academic grades between the groups (p<0.005). There was greater improvement in the mean results of students’ grades (p=0.001) and less variation between students in group 2 compared to group 1 (p<0.05). Conclusion: Online learning was found to be an effective teaching method for physical therapy students during the coronavirus disease-2019 pandemic with respect to basic medical knowledge. However, its impact on clinical and practical skills of the students was not confirmed. Keywords: COVID-19, Pandemic, Online learning, Student performance, Physical therapy.